Connecting Energy Input With Ionospheric Upflow and Outflow - Glocer, A.; Daldorff, L. K. S. (Journal of geophysical research. Space physics, 2022)
The connection between energy inputs and the generation of ion upflows and outflows is a topic of keen scientific interest and the subject of a number of empirical studies. Despite this interest, it remains uncertain how different ion species respond to energy input, what defines the upper and lower bounds of the ion flux, and what role solar illumination plays in regulating the relationship between energy input and ion upflows/outflows. This work simulates how ion flux scales with low and high altitude energization, and to a combination of both. Furthermore, we examine the influence of solar illumination on these relationships by considering how the scaling of ion flux with energy input changes over the solar cycle, comparing solar minimum and maximum, as well as how they change from day to night conditions. We find O+ flux tends to respond more strongly to energy inputs than H+ flux, with the O+ flux often exhibiting a lower activation energy and a greater dynamic range. The lower bound of the ion flux at 4,000 km is typically defined by the polar wind H+, although O+ upflows can dominate at low altitudes in the presence of significant frictional heating of the ion gas or soft electron precipitation. However, when significant soft electron precipitation and wave‐particle interactions are present simultaneously the lower bound of the ion flux at 4,000 km is defined by the O+. Finally, we find a difference between the steady state response of the outflow to energy input and the peak response. Key Points O+ flux tends to respond more strongly to energy inputs than H+ flux The lower bound of the ion flux at 4,000 km is typically defined by the polar wind H+ except when large e− precipitation is present The peak response of the outflow to energy input can be different than the steady state response